P066 ON104, a novel bioengineered antibody targeting oxidized Macrophage Migration Inhibitory Factor (oxMIF) shows efficacy in two distinct models of experimental colitis. (30th January 2023) - Ferhat, M; Mangano, K; Nicoletti, F; Landlinger, C; Michael, T
Abstract: Background: Macrophage Migration Inhibitory Factor (MIF) is a pleiotropic inflammatory cytokine and a primary counter-regulator of glucocorticoids (GCs) that emerged as a pivotal regulator of chronic inflammation including inflammatory bowel diseases (IBD). MIF occurs in two immunologically distinct, conformational isoforms: reduced MIF, ubiquitously present in various tissues and the circulation of healthy subjects, and oxidized MIF (oxMIF), described as the pathogenic and druggable isoform of MIF. In this study we evaluated the anti-inflammatory effects of the anti-oxMIF antibody ON104 in two different mouse models of colitis. Methods: The fully human antibody ON104, which specifically targets oxMIF, was generated by advanced antibody engineering technology. The therapeutic potential of the Fc-silenced ON104 antibody was tested in two different models of colitis in mice: the acute model of DSS-induced colitis in C57BL/6 mice and the chronic model of adoptive T-cell transfer in SCID mice. At disease induction, ON104 was given twice a week for 8 weeks (chronic colitis) or three times for 1 week (acute colitis). Body weight, stool consistency, and rectal bleeding were assessed to evaluate colitis severity. At the end of the DSS-induced colitis model, colons were dissected for immuno-histological examinations. Results: ON104 antibody, specifically directed against oxMIF, was completely devoid of Fcγ receptors binding and cytokine triggering in the presence of immune cells. Treatment with ON104 in the chronic colitis model substantially attenuated clinical signs of colitis by thwarting body weight loss and restoring stool consistency. In the acute DSS colitis model, oxMIF neutralization was able to reduce mucosal thickness and colonic immune cell infiltration compared to vehicle-treated mice. Conclusion: Our findings substantiate the role of oxMIF in the pathogenesis of experimental colitis. Thus, targeting oxMIF may represent a new and promising treatment option for IBD.